Administration of Aesthetics : Censorship, Political Criticism, and the Public Sphere. - Burt, Richard (Cultural politics., 1994)
The ""new"" censorship of the arts, some cultural critics say, is just one more item on the ""new"" Right's agenda, and is part and parcel of attempts to regulate sexuality, curtail female reproductive rights, deny civil rights to gays and lesbians, and privatize public institutions. Although they do not contest this assessment, the writers gathered here expose crucial difficulties in using censorship, old and new, as a tool for cultural criticism. Focusing on historical moments ranging from early modern Europe to the postmodern United States, and covering a variety of media from books and pai.